KEDUDUKAN GURU SEBAGAI PENDIDIK - M. Yusuf Seknun (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2012)
Abstract: Teacher become a factor that determines the quality of education because they directly face to face with the students in the classroom teaching and learning process. Teacher has complicated duties and responsibilities in carrying out his/her professional duties. The teacher, therefore, should have good competence as well as know his/her own right and responsibility so that he/she becomes the real professional teacher. Teacher is obliged to help the child's development toward good maturity in accordance with Islamic teaching. As a professional position, the teacher is required to have special skills. Therefore, he/she should be given certain right so that he/she can fulfill his/her own duty and responsibility. Professional teacher is required to have specific competency, which include paedagogic, personality, social, and professional competencies.Abstrak: Guru menjadi faktor yang menentukan mutu pendidikan karena guru berhadapan langsung dengan para peserta didik dalam proses pembelajaran di kelas. Guru dalam menjalankan tugas profesionalnya mempunyai tugas dan tanggung jawab yang tidak ringan. Untuk itu, guru harus memiliki dan menguasai kompetensinya dan sekaligus mengetahui hak dan kewajibannya sehingga ia menjadi sosok guru yang betul-betul profesional. Guru berkewajiban membantu perkembangan anak menuju kedewasaan yang sesuai dengan ajaran Islam. Guru sebagai jabatan profesional yang dituntut memiliki keahlian khusus, untuk itu, guru harus diberikan hak-hak tertentu sehingga mereka dapat memenuhi tugas dan tanggung jawabnya. Guru profesional dituntut memiliki kompetensi-kompetensi khusus yang meliputi; paedagogik, kepribadian, sosial, dan profesional.